2018
DOI: 10.12691/msme-5-1-1
|View full text |Cite
|
Sign up to set email alerts
|

Precipitation Behavior in an Al-Mg Alloy with High Mg Composition

Abstract: We have investigated the precipitation phenomena which occur at high aging temperatures in an Al-Mg alloy with high Mg concentration by means of Vickers hardness (HV) testing, differential scanning calorimetry (DSC), transmission electron microscopy (TEM) and analytical scanning transmission electron microscopy (STEM-EDX). It was found that the hardness and heat changes are closely correlated, and that the size of the exothermic heat peak depends on the quantity of β'-phase formed during isothermal aging prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Huang et al [34] found that the interaction between the vapor plume and the keyhole is considered to induce the oscillation of keyhole and vapor plume. Depending on the alloying elements, the 5xxx series alloys can form different phases [35,36]. If the magnesium content is higher than 3.5 wt.% in Al alloy then precipitates of β-phase (Mg 2 Al 3 ) can be formed [37].…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al [34] found that the interaction between the vapor plume and the keyhole is considered to induce the oscillation of keyhole and vapor plume. Depending on the alloying elements, the 5xxx series alloys can form different phases [35,36]. If the magnesium content is higher than 3.5 wt.% in Al alloy then precipitates of β-phase (Mg 2 Al 3 ) can be formed [37].…”
Section: Introductionmentioning
confidence: 99%